We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
177
4
avatar

Find constants A, B, and C so that \(\frac{4x}{(x - 5)(x - 3)^2} = \frac{A}{x - 5} + \frac{B}{x - 3} + \frac{C}{(x - 3)^2}\)

 Mar 10, 2019
 #1
avatar+6046 
+1

\(\dfrac{4x}{(x-5)(x-3)^2} = \dfrac{A(x-3)^2+B(x-5)(x-3)+C(x-3)}{(x-5)(x-3)^2}\)

 

\(4x = A(x^2-6x+9) + B(x^2-8x+15)+C(x-3)\\ 4x = x^2(A + B) + x(-6A-8B+C)+(9A+15B-3C)\)

 

\(A+B=0\\ (-6A-8B+C)=4\\ (9A+15B-3C) = 0\)

 

\(\text{I leave you to solve for }A,B,C\)

.
 Mar 10, 2019
 #2
avatar+105327 
0

        4x                              A                   B                   C

____________  =        _______    +     _____    +    _______       

(x - 5)(x - 3)^2               (x - 5)                (x - 3)          (x - 3)^2

 

 Multiply through by (x - 5) ( x -3)^2

 

4x   =    A(x - 3)^2   +  B(x- 5)(x - 3)  + C(x - 5)      simplify

 

4x  =  A(x^2 -  6x + 9)  + B(x^2 - 8x + 15)  + C(x - 5)

 

4x  = (A + B)x^2    + (-6A - 8B + C)x + (9A + 15B - 5C)

 

Equating coefficients, we have

 

A + B  =  0     ⇒   B = -A      (1)    

-6A - 8B + C  = 4    (2)

9A + 15B - 5C =  0     (3)

 

 

Subbing  (1)  into (2)  and (3)   we have

 

-6A + 8A + C   = 4   ⇒   2A + C  =  4   ⇒   6A + 3C = 12    (4)

9A - 15A - 5C  = 0  ⇒  -6A - 5C = 0        (5)     

 

Add (4) and (5)

 

-2C =  12

C = -6

 

And using (4) to find (4)

6A + 3(-6)  = 12

6A - 18 = 12

6A = 30

A = 5

 

And B = -A =    -5

 

So   (A,B,C)  = (5, -5, - 6)

 

 

 

cool cool cool

 Mar 10, 2019
edited by CPhill  Mar 10, 2019
 #3
avatar+4330 
+3

Yep, this is known as the "Partial Fraction Decomposition." 

 Mar 10, 2019
 #4
avatar+23521 
+3

Find constants A, B, and C so that

\(\large{\dfrac{4x}{(x - 5)(x - 3)^2} = \dfrac{A}{x - 5} + \dfrac{B}{x - 3} + \dfrac{C}{(x - 3)^2}}\)

 

\(\begin{array}{|lrcll|} \hline & \dfrac{4x}{(x - 5)(x - 3)^2} &=& \dfrac{A}{x - 5} + \dfrac{B}{x - 3} + \dfrac{C}{(x - 3)^2} \quad | \quad \cdot (x - 5)(x - 3)^2 \\\\ & \mathbf{4x} &\mathbf{=}& \mathbf{A(x - 3)^2 + B(x - 5)(x - 3) + C(x - 5)} \\\\ \hline x=3: & 4\cdot 3 &=& A\cdot 0 + B\cdot 0 + C(3 - 5) \\ & 12 &=& -2C \\ & \mathbf{C} &\mathbf{=}& \mathbf{-6} \\\\ x=5: & 4\cdot 5 &=& A(5 - 3)^2 + B\cdot 0 + C\cdot 0 \\ & 20 &=& A\cdot 2^2 \\ & 20 &=& 4A \\ & \mathbf{A} &\mathbf{=}& \mathbf{5} \\\\ x=0: & 4\cdot 0 &=& 5(0 - 3)^2+B(0 - 5)(0 - 3)-6(0 - 5) \\ & 0 &=& 45 +15B+30 \\ & 15B &=& -75 \\ & \mathbf{B} &\mathbf{=}& \mathbf{-5} \\ \hline \end{array}\)

 

 

laugh

 Mar 11, 2019

35 Online Users

avatar